A novel cervical spine protection device for reducing neck injuries in contact sports: design concepts and preliminary in vivo testing - Caravaggi, P.; Leardini, A.; Belvedere, C.; Siegler, S. (Sports Biomechanics, 2020)
Head and neck injuries are common in contact sports such as American football. Different mechanisms can produce such injuries, including compressive impact forces on the crown of the helmet with the neck in a flexed chin-down position. The aim of this paper was developing and testing a novel Cervical Spine Protection Device (CSPD) designed to keep the neck within its safe physiological range. The cervical spine range of motion (ROM) of ten participants was measured under four conditions: free; wearing a football gear; wearing the CSPD; and wearing the CSPD underneath the gear. The CSPD was tested in terms of passive and active restraint of head motion, and for its capability to improve endurance time of the neck extensor muscles. Wearing the CSPD resulted in a significant 40-60% reduction in ROM across the three anatomical planes, and in increased endurance of the neck extensor muscles (FREE: 114 ± 57 s; CSPD: 214 ± 95 s; p = 0.004). In quasi-static loading conditions the CSPD was capable of keeping the neck within its physiological range, thus it may be used to decrease the risk of severe injuries due to dangerous chin-down positions.